In-particle stem-loop RT-qPCR for specific and multiplex microRNA profiling - Jung, Seungwon; Kim, Won Jin; Kim, Bong Kyun; Kim, Junsun; Kim, Mi Jung; Kim, Kwang Pyo; Kim, Sang Kyung (ELSEVIER ADVANCED TECHNOLOGY, 2020)
Here we report a novel method of microRNA (miRNA) profiling with particle-based multiplex quantitative reverse transcription polymerase chain reaction (RT-qPCR). To achieve target-specific reaction in a particle, the stem-loop RT primer and forward primer for each target miRNA were chemically immobilized to the particle. Target-specific cDNA synthesis proceeds with the stem-loop RT primer and then qPCR subsequently proceeds with the forward primer to rapidly achieve a quantitative result. High-fidelity multiplex assay was also accomplished in a single PCR process by loading multiple particles for each specific miRNA. The method for primer supply in the particles, involving confinement of the target-specific RT and PCR primers in the matrix of particles, led to the reduction of nonspecific reactions and improved the selectivity of the miRNA assay while minimizing labor in a multiple target assay. Specifically, this particle-based assay enabled the differentiation of mature miRNA from precursor with selectivity of 270:1 in terms of amplification speed. This advanced method also showed good discrimination among highly homologous let-7 family members, with cross-reaction rates of less than 5%. We demonstrated a very simple process of five-plex miRNA profiling in total RNA, and the measured changes in expression level were consistent with those from a conventional singleplex method.
Keywords: SMALL RNAS; EXPRESSION; PCR; QUANTIFICATION